Study of medicines' market for the treatment of seborrheic dermatitis of the pilar part of head - V. A. Solodovnik; N. O. Tkachenko; S. А. Gladisheva; Fadi Al Zedan (Zaporozhye State Medical University, 2018)
Modern arsenal of medicines and cosmetics used for the therapy of seborrheic dermatitis of the pilar part of head is various enough. Today pharmaceutical market keeps developing and constitutes a complex system that causes the necessity of its investigation and forming the informational base concerning the dynamics of assortment, prices and availability of medicines. The aim of work is forming the informational file about medicines and cosmetics which are used in treatment of seborrheic dermatitis of the pilar part of head and advisability substantiation of the creation of new medication with Octopirox on the base of marketing analysis. Materials and methods. As informative materials we used: the State register of medications of Ukraine; reference book of medications «Compendium on-line»; internet resources on the search of medications in the pharmacies of Ukraine "GeoApteka" and "Tabletki.ua". A marketing method, monitoring methods, logical generalization, groupment and graphic methods were applied in-process of research. Results. Complex marketing evaluation of the Ukrainian pharmaceutical market of medications used for the therapy of seborrheic dermatitis of the pilar part of head was carried out taking into account heterogeneous structure in two trends: medicines and cosmetics. Conclusion. Modern arsenal of medicines was organized in two trends: segment of medicines consists of 26 medications of D01A subgroup "Antifungals for topical use" and D11A subgroup "Other dermatologic medications"; "КС" segment has 71 cosmetics (cosmetics with Octopirox prevail - 12 propositions). In form of making, the liquids prevail - shampoo, tonics, solutions, serums. All tools concerning "Order of dispensing" are available without a prescription but before their using the doctor's advice taking into account individuality of each patient is needed. The analyzable market segment is characterized by the deficiency of combined drugs and no great amount of proposals of domestic producers. Next scientific research outlook. All referred above determines perspective direction and advisability of the creation of the new medication with Octopirox.